Pulp necrosis following luxated injury to teeth in a patient with uncontrolled type II diabetes mellitus: a case report - Haneol Shin; Seung-Jong Lee; Il-Young Jung; Chan-Young Lee (Korean Academy of Conservative Dentistry, 2012)
Patients with diabetes mellitus show delayed wound healing and increased susceptibility to infection. Therefore, the effects of diabetes on pulpal and periodontal healing should be taken into consideration when treating diabetic dental traumatized patients. This case presents the treatment for dental traumatized 20 yr old female with uncontrolled type II diabetes. The traumatized upper central incisors had showed pulpal healing in early days. However, 7 mon after the trauma, the teeth had been diagnosed with pulp necrosis with apical abscess. Eventually, non surgical root canal treatment on the teeth had been performed.